2006
DOI: 10.1056/nejmoa043891
|View full text |Cite
|
Sign up to set email alerts
|

Mucus Clearance and Lung Function in Cystic Fibrosis with Hypertonic Saline

Abstract: In patients with cystic fibrosis, inhalation of hypertonic saline produced a sustained acceleration of mucus clearance and improved lung function. This treatment may protect the lung from insults that reduce mucus clearance and produce lung disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
480
5
17

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 617 publications
(533 citation statements)
references
References 19 publications
23
480
5
17
Order By: Relevance
“…Similar to the blood dip experiments, we immersed the silicone oil-coated endoscopes into porcine mucin solutions with a concentration (17 wt./vol%) typically found in cystic fibrosis patients: a patient population known to have an excess of extremely sticky lung secretions (34,35). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the blood dip experiments, we immersed the silicone oil-coated endoscopes into porcine mucin solutions with a concentration (17 wt./vol%) typically found in cystic fibrosis patients: a patient population known to have an excess of extremely sticky lung secretions (34,35). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…35 The observation of a decrease in mucin gel strength is consistent with recent studies which have shown that inhalation of hypertonic saline aids in mucus clearance for cystic fibrosis patients. 36 Observation of the Nearly Critical Gel at pH 4. To ensure that the rheological changes in the gel properties presented above were entirely driven by pH rather than ionic strength, which does vary slightly with the pH of the buffer solution, rheology experiments at varying pH were repeated on samples of identical ionic strength (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Another drug, Moli1901, works by increasing the activity of non-CFTR chloride channels, and there is evidence of clinical efficacy for these compounds [96]. Inhalation of hypertonic saline preceded by a bronchodilator [97,98] has recently been shown to improve lung function in CF patients with varying severities of lung disease, and as a result, there are now studies underway looking at the efficacy of hypertonic saline in infants with CF. Finally, numerous papers have recently appeared claiming to have identified genetic modifiers that influence the course of CF lung disease and thus are potential targets for clinical interventions [99].…”
Section: Targeting the Consequences Of Defective Cftr Functionmentioning
confidence: 99%
“…Restoration of salt transport Four drugs in phase II or III trials a , encouraging results with Denufosol (P2Y2 receptor agonist) from phase II trial [94,95] Mucus treatment Two established therapies: recombinant human DNase (Pulmozyme ® ) [18,62,65] and hypertonic saline inhalation [97] Non-CFTR-specific interventions…”
Section: Strategymentioning
confidence: 99%